Determinants of Profitability in Food and Beverage Companies: Faktor-faktor yang Mempengaruhi Keuntungan dalam Perusahaan Makanan dan Minuman - Nindy Ellyn; Eny Maryanti (Indonesian Journal of Law and Economics Review, 2025)
General Background Profitability is a key indicator of corporate performance and sustainability, particularly in manufacturing industries. Specific Background Food and beverage companies face dynamic operational and financial conditions that require effective financial management to maintain profitability. Knowledge Gap Previous studies report inconsistent findings regarding financial ratios and growth variables associated with profitability in this sector. Aims This study aims to examine the relationship between company growth, sales growth, inventory turnover, and profitability in food and beverage companies listed on the Indonesia Stock Exchange. Results The findings show that selected financial and growth variables exhibit varying relationships with profitability as measured by return on assets. Novelty This research provides contextual evidence by focusing on a specific industrial sector and observation period using updated financial data. Implications The results offer empirical insights for management in evaluating financial performance and serve as a reference for future research on profitability determinants in manufacturing companies. Keywords: Profitability, Return on Assets, Company Growth, Sales Growth, Inventory Turnover Key Findings Highlights: Financial growth indicators show differentiated relationships with corporate returns Inventory management remains a relevant aspect of financial performance Sector specific analysis reveals contextual profitability patterns